Capturing degrees of centring of refugees in an academic literacy course in post-Apartheid South Africa: A retrospective look at course design through the lens of Actor-network Theory - Moeain Arend; Aditi Hunma; Minga Kongo (Perspectives in Education)
In 2018, we received state funding for ‘curriculum reform’ to design an academic literacy course that would orient students to legitimate ways of reading and writing in the academy while fostering critical citizenship. Thus, drawing on the view of literacy as a social practice, the course design was shaped around relatable content, in this case, the issue of border-crossing. At that time, some media coverage and popular opinion perpetuated an essentialist view of refugees as a socio-economic and health threat in South Africa and other parts of the globe. Unfortunately, this is still prevalent locally and elsewhere. We understand border-crossing as both physical and conceptual while also acknowledging the internal displacement as well, dating back to the apartheid regime when borders were created within South Africa along ‘ethnic’ and ‘racial lines’. We also acknowledge how the social death (Patterson, 1982) experienced by some previously marginalised South Africans has had repercussions on how they view refugees. In this social context, we sought to design and implement an academic literacy course that was socially responsive in post-apartheid South Africa, marked by rapid social changes, and coupled with cases of xenophobia targeting refugees from other parts of Africa. To analyse how the course responded to these broader issues, we employed an actor-network theory lens, drawing specifically on Callon’s (1984) description of translation, the process through which a stable actornetwork is created. We took a retrospective look at the course over five years, focusing on the changes from the first to subsequent iterations. In our reflections, we superimposed Callon’s (1984) four moments of translation, namely problematisation, interessement, enrolment and mobilisation, on the design process. In doing so, we surfaced the design and strategies to create a stable actornetwork of associations between human and non-human actors. Through our retrospective look, we argue that for the design of a stable network, in other words, a practical academic literacy course that responds critically to cross-border migration through reading and writing, “the refugee” must be implicated in these four moments. Furthermore, we highlight how “the refugee” oscillated between various “degrees of centring” during these moments as part of the strategies employed by translators (course designers) to stabilise the network.